Altitude Geo Hash Method for Location Based Systematized Billing for Packers and Movers - Pappula Madhavi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Maps play an important role in representing spatial and temporal locations and producing large volumes of data. Today’s world is connected to many Internet devices with GPS (Global Positioning System) and IoT (Internet of Things) to collect and analyze massive amounts of data. A Geo-hash code is an alphanumeric code that expresses each location for unique identification. Location based services identify mobile locations geographically. We can generate a Geo-hash code with latitude and longitude as well as the altitude of a location. A Geo-hash with altitude generates secure code for location-based devices to identify a particular user. A method is generated to identify the distance between two locations by using the Haversine distance, which is distance between two points of a sphere on the surface of Earth in angular length and can identify the payment charges for packers and movers. This manuscript provides a detailed description of the Geo-hash with altitude (Alt Geo Hash) unique code and a feasible payment method for users to relocate items from one location to another. LBS (Location Based Services) play an essential role in maintaining public life structure, leakage of credentials from lack of standardized apps and maintaining the security of order payments. This method provides an agreeable payment to users for shifting goods and avoiding fraudsters from unwanted minor parties.